If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y + 3xy + 2y = 0 Reorder the terms: 3xy + 5y + 2y = 0 Combine like terms: 5y + 2y = 7y 3xy + 7y = 0 Solving 3xy + 7y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7y' to each side of the equation. 3xy + 7y + -7y = 0 + -7y Combine like terms: 7y + -7y = 0 3xy + 0 = 0 + -7y 3xy = 0 + -7y Remove the zero: 3xy = -7y Divide each side by '3y'. x = -2.333333333 Simplifying x = -2.333333333
| x/-23 | | -8=-(x-8) | | 20m=8 | | 49a^7b^4-84a^5b^4=0 | | S=p+I | | 2y/8y^(n-1) | | 6x-16=-22+6x | | 1=3.33 | | Y=8+16 | | 1.9(x-2.7)= | | y=2x^2+12x+21 | | 8/w=6/54 | | 3x-2(8-x)=-16 | | 5x(-3x)=-15x^2 | | 7.20x+5.50y=52.75 | | k/21=14/49 | | 3+6x=5x | | 2b-3=6 | | 13c^5d^5-169cx^4d^3=0 | | 10/16=15/p | | Y=150+10 | | 71/4×1/18 | | C-12=2 | | 4/5=m/35 | | 8+a=7 | | 15(6x-8)=14(x-5)-2 | | x-9-51=918 | | 2a-4=5 | | 6*11y/2 | | 8d=4 | | -16t^2+126t=126+5 | | -16t^2+126t=136+5 |